2018
DOI: 10.5430/jnep.v9n2p1
|View full text |Cite
|
Sign up to set email alerts
|

The journey of having scabies–A qualitative study

Abstract: Background and objective: Scabies is considered to be a common skin infection in the field of dermatology, but it is also, by the World Health Organization referred to as a neglected disease. It can cause complications such as secondary infections linked to the development of glomerulonephritis and chronic kidney disease. Furthermore, scabies is associated with stigma, shame and social isolation. To date no qualitative study, has explored this area in depth. The aim of this study was to gain an in-depth unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Proper management of the surrounding environment is important and time-consuming, and may have a negative impact on the daily lives of patients. 3…”
Section: Introductionmentioning
confidence: 99%
“…Proper management of the surrounding environment is important and time-consuming, and may have a negative impact on the daily lives of patients. 3…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patients tried to hide their warts in social contexts. It is well known that patients with skin diseases often have feelings of being stigmatized (12,13). In the case of warts, the stigma may be related to the fact that it is caused by an infection and is thus contagious (14).…”
Section: Discussionmentioning
confidence: 99%
“…When there is uncertainty on the cause, due to patients' inability to understand the association mentioned above or lack of provision of information by physicians, patients tend to try various treatment modalities and often become dissatisfied with the outcomes. A qualitative study on patients with scabies similarly revealed uncertainty about their illness and diagnosis, poor understanding of their illness‐related events and insecurity 41 . In contrast, sharing information about illness is known to improve the doctor–patient relationship and patient satisfaction 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study on patients with scabies similarly revealed uncertainty about their illness and diagnosis, poor understanding of their illness‐related events and insecurity. 41 In contrast, sharing information about illness is known to improve the doctor–patient relationship and patient satisfaction. 42 According to Mishel's Theory of Uncertainty in Illness, healthcare professionals can reduce the uncertainty by providing information on the causes and consequences of symptoms and increase a patient's clarity and knowledge of the illness.…”
Section: Discussionmentioning
confidence: 99%